2014
DOI: 10.1182/blood-2013-10-533844
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the development of acute myeloid leukemia in CBL syndrome

Abstract: We describe the development of acute myeloid leukemia (AML) in an adult with CBL syndrome caused by a heterozygous de novo germline mutation in CBL codon D390. In the AML bone marrow, the mutated CBL allele was homozygous after copy number-neutral loss-of-heterozygosity and amplified through a chromosomal gain; moreover, an inv(16)(p13q22) and, as assessed by whole-exome sequencing, 12 gene mutations (eg, in CAND1, NID2, PTPRT, DOCK6) were additionally acquired. During complete remission of the AML, in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…In both cases, sucking and swallowing difficulties, frequently observed in context of orofacial dyspraxia following stroke involving insular regions, hypotonia, mild motor and speech delay, were attributed to ancient strokes in MCA territories that were seen on initial MRI. Other signs such as transitory coagulation defects without bleeding tendency in trio 1 proband—coagulation defects were reported so far in one CBL- mutated patient27—and café-au-lait spots in trio 3 proband were subtle and did not lead neuropaediatricians to consider a diagnosis of RASopathy. Indeed, no ‘red flag’ suggestive of a RASopathy has been identified by neuropaediatricians in both girls, in whom MMA was the hallmark manifestation at diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…In both cases, sucking and swallowing difficulties, frequently observed in context of orofacial dyspraxia following stroke involving insular regions, hypotonia, mild motor and speech delay, were attributed to ancient strokes in MCA territories that were seen on initial MRI. Other signs such as transitory coagulation defects without bleeding tendency in trio 1 proband—coagulation defects were reported so far in one CBL- mutated patient27—and café-au-lait spots in trio 3 proband were subtle and did not lead neuropaediatricians to consider a diagnosis of RASopathy. Indeed, no ‘red flag’ suggestive of a RASopathy has been identified by neuropaediatricians in both girls, in whom MMA was the hallmark manifestation at diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…4,6 Investigation of the mechanisms underlying the disease progression has identified genetic alterations, such as mutations in the Asxl1 (additional sex combslike 1), Setbp1 (SET-binding protein 1), and NPM1 (nucleophosmin) genes [43][44][45][46] ; however, little is known about genes whose expressional changes are responsible for disease evolution. By employing retrovirusmediated mutagenesis, we identified Evi1, a gene encoding a transcription factor involved in normal hematopoiesis and leukemogenesis, 28 as a cooperative gene with Cbl Q367P and demonstrated that overexpressed EVI1 synergized with CBL Q367P to develop AML.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified CBL mutations in 5 –10 % of CBF-AML 59 . CBL is also frequently mutated in myelodysplastic/myeloproliferative neoplasms, but rarely mutated in other types of de novo AML 1018 .…”
Section: Introductionmentioning
confidence: 99%